Baldness and testicular cancer: the EPSAM case–control study. (20th January 2016) - Moirano, G.; Zugna, D.; Grasso, C.; Lista, P.; Ciuffreda, L.; Segnan, N.; Merletti, F.; Richiardi, L.
Summary: The etiology of testicular cancer is largely unexplained. Research has mainly focused on prenatal exposures, especially to sex hormones, while less attention has been paid to exposures that may act also postnatally. As baldness has been previously associated with testicular cancer risk we focused on baldness and body hairiness, which are both associated with androgen activity. We used data of the Postnatal Exposures and Male Health (EPSAM) study, a case–control study on testicular cancer conducted in the Province of Turin, Italy, involving cases diagnosed between 1997 and 2008. Information was collected using mailed questionnaires. Analyses included 255 cases and 459 controls. We calculated ORs and 95% CIs to estimate testicular cancer risk among those who developed baldness and among those with body hairiness. We found an inverse association between testicular cancer and baldness (OR: 0.67, 95% CI: 0.46–0.98) and body hairiness (OR: 0.78, 95% CI: 0.53–1.16), although the latter had wider CIs. The inverse association between baldness and testicular cancer is consistent with the results from previous studies. These results suggest that androgens activity may influence testicular cancer risk.